Speech Activity of Cadet-girls of the Academy of the Federal Penitentiary System of Russia as a Factor of Forming Their Professional Competence - Bespalova, Tatyana (East European Journal of Psycholinguistics, 2015)
The article is devoted to research of the display in the speech of cadet-girls.  Peculiarities of their speech are presented at the pretext level, linguistic characteristics of the texts are described as products of individual speech activity and psychological components of their speech operations. Being the representative of the personality, the speech activity is showed to be the reflection of the individual peculiarities of a person. The profession of the penitentiary psychologists predetermines the developing of the speech activity of the cadet-girls, forming the professional competence of the future internal service officials. The texts of the cadet-girls is notable for their complexity, descriptive nature, logicality, completeness, emotionally rich in positively coloured lexical units,  egocentric orientation of the expressions. At the same time they involve grammatical mistakes, reflect the display of volitional  efforts, an attempt to perception, analysis and systematic  activity. The peculiarities of the display of cadet-girls personal characteristics are revealed both in linguistic and in psychological aspects, as they  stipulate the developing of their cogitative, emotional-volitional and  motivational areas, and the conditions of the forming of their  individuality, that may be the illustration not only of their common educational and cultural level, but also that of speech, providing for the forming of the professional speech formation.ReferencesMiroshkina, N. (1992). Tipy samoregulyatsii i individual’nye razlichiya v rechevoydeyatel’nosti studentov [The types of self-regulation and individual peculiarities of the students`speech activity]. Ph.D. thesis. Мoscow: Peoples’ Friendship University of Russia.Fomina, N. (2002). Svoystva Lichnosti i Osobennosti Rechevoy Deyatelnosti [PersonalityTraits and Peculiarities of Speech activity]. Ryazan: Uzorochye.